The Impact Of Tourism On Land Conversion In Kerobokan Kelod Village, North Kuta District, Badung Regency - I Gusti Agung Ngurah Maha Adi Putra; I Nyoman Sukma Arida; I Made Adhika (International journal of technology and education research, 2026)
This study examines the impact of tourism on land-use conversion from agriculture to commercial purposes in Kerobokan Kelod Village, North Kuta District, Badung Regency, Bali. The area has undergone significant transformation due to rapid tourism development, marked by the conversion of productive agricultural land into villas, hotels, and restaurants. The aim of this research is to identify the resulting impacts and formulate mitigation strategies to balance tourism growth with environmental sustainability and the preservation of local socio-cultural values. The research adopts a qualitative descriptive approach supported by quantitative data, collected through in-depth interviews, direct observation, and documentation. Data analysis techniques involve SWOT analysis and the Analytical Hierarchy Process (AHP). The findings reveal that while land conversion has contributed to increased income and employment opportunities, it has also led to the loss of agricultural regeneration, economic dependence on the tourism sector, and environmental degradation. The SWOT analysis generated 20 alternative strategies categorized based on strengths, weaknesses, opportunities, and threats. AHP prioritization identified three main strategies: (1) implementing land zoning regulations and investment monitoring to prevent speculation and ensure ecological sustainability; (2) developing community-based agrotourism to preserve culture and diversify the local economy; and (3) providing training and skills development programs to enhance the competitiveness of the local workforce. This study highlights the importance of participatory tourism governance rooted in local wisdom to ensure that economic growth does not compromise environmental resilience and cultural identity.